THE PROTECTION OF REFUGEES UNDER INTERNATIONAL LAW - Aditya Rivaldi; Lena Farsia (Fakultas Hukum Universitas Syiah Kuala, 2018)
The protection of refugee is the duty to all civilized nation in the world. It is a human rights and humanitarian value that every state must take responsible with. Among several kinds of protections, there is one of the most important one which is stated in article 33 of the 1951 Convention on the Status of Refugee, the non-refoulment principle. This principle has became customary international and also has been received the jus cogens status. The purpose of this thesis is to understand the role of Jus cogens principle of non-refoulment will effect Indonesia in giving assistance to the Rohingya refugees and to understand the protection given by Indonesia government to the Rohingya refugees. This research uses normative empirical research.The data in this study were obtained through the research libraries to acquire secondary data by way of studying the legislation, books, the internet and other scholarly works related to the problems of the research. Furthermore, fieldwork conducted for obtaining primary data by interviewing respondents and informants. The results of the research showed that the non-refoulment principle gives no effect to Indonesia in giving assistance to the Rohingya refugees. Indonesia actions were done base on humanitarian value, Indonesia Constitution, and Pancasila value, instead of 1951 Convention on the Status of the Refugee. Accordingly with the result above, it is suggested to the government of Indonesia, to produce a new clear legislation on the management of the international refugee. And then, to assimilate and promote the 1951 Convention on the Status of Refugee as an international standard in assisting refugee to the Indonesian bodies that concern about it. Furthermore, to Indonesia government particularly Aceh suggested that to produce a new regulation in regard with the emergency respond and also to maintain all the refugee facilities that had been built by volunteers or others country.